Effect of active versus passive recovery on metabolism and performance during subsequent exercise - McAinch, A. J.; Febbraio, M. A.; Parkin, J. M.; Zhao, S.; Tangalakis, K.; Stojanovska, L.; Carey, M. F. (International Journal of Sport Nutrition and Exercise Metabolism, 2004)
This study tested the hypothesis that active recovery between bouts of intense aerobic exercise would lead to better maintenance of exercise performance in the second bout of exercise. Seven trained men on 2 separate occasions (VO2peak = 58.3 ± 9.4 ml · kg-1 · min-1) performed as much work as possible during two 20-min cycling exercise bouts, separated by a 15-min recovery period. During passive recovery (PR), subjects rested supine, while during active recovery (AR) subjects continued to cycle at 40% VO2peak. Muscle biopsies and blood samples were obtained. Neither muscle glycogen or lactate was different when comparing AR with PR at any point. In contrast, plasma lactate concentration was higher (p < .05) in PR versus AR during the recovery period, such that subjects commenced the second bout of intense exercise with a lower (p < .05) plasma lactate concentration in AR (4.4 ± 0.7 vs. 7.7 ± 1.4 mmol · L-1 following AR and PR, respectively). Work performed in Bout 2 was less than that performed in Bout 1 in both trials (p < .01), with no difference in work performed between trials. These data do not support the benefit of AR when compared to PR in the maintenance of subsequent intense aerobic exercise performance.